Relative risk values of age, acrolein, IL-6 and CRP as markers of periventricular hyperintensities: a cross-sectional study. Issue 8 (13th August 2014) - Abe, Arata; Nishiyama, Yasuhiro; Harada-Abe, Mina; Okubo, Seiji; Ueda, Masayuki; Mishina, Masahiro; Katayama, Yasuo
Abstract : Objective: Brain white matter hyperintensities can be divided into periventricular hyperintensity (PVH) and deep-and-subcortical white matter hyperintensity (DSWMH); the former contributes more to cognitive dysfunction and infarction risk. We conducted the present investigation to define the relationship between PVH and DSWMH. Design: Cross-sectional study. Setting: University hospital. Participants: We prospectively enrolled 228 healthy Japanese volunteers with relative risk values (RRVs) >0.5. Primary outcome measures: We investigated whether it is possible to use the RRV to predict PVH and DSWMH. Results: Among 228 volunteers, 103 (45.1%) and 157 (68.8%) exhibited PVH and DSWMH, respectively. Age, body mass index and PVH were significant independent determinants of RRV. A significant OR for PVH was noted in the highest RRV tertile compared with the lowest, after adjusting for potential confounding factors. A significant OR for high predicted PVH risk was found for RRV levels as well. Conclusions: Elevated RRV levels were significantly associated with increased predicted PVH, suggesting that measuring the plasma protein-conjugated acrolein, interleukin 6 and C reactive protein levels may be useful for identifying Japanese at high risk for PVH.